Perspectives and attitudes of breastfeeding women using herbal galactagogues during breastfeeding: a qualitative study - Sim, Tin Fei; Hattingh, H. Laetitia; Sherriff, Jill; Tee, Lisa (BioMed Central Ltd., 2014)
Some herbal galactagogues have gained reputation and recognition by the public and health professionals as alternative approaches to increase breast milk supply. This study explores the perspectives and attitudes of breastfeeding women towards the use of herbal galactagogues while breastfeeding, their experiences, and why and how they have chosen an alternative option over conventional treatments to enhance breastfeeding performance. This exploratory research was conducted through in-depth semi-structured interviews with women living in Perth, Western Australia, who were using one or more herbal galactagogues during breastfeeding. Purposeful and subsequent snowball sampling methods were employed to recruit participants. All interviews, facilitated by an interview guide, were audio-recorded, then transcribed verbatim. Thematic analysis was used to analyse qualitative data to construct themes and subthemes.The perspectives and attitudes of the 20 participants are classified under three main headings: i) use of herbal medicines during breastfeeding, ii) available herbal medicines resources, and iii) level of breastfeeding support received. Throughout the interviews, participants described how their perseverance and determination to breastfeed, as well as concerns over breastfed infants’ safety with conventional treatments, influenced their choice of therapy. A sense of self-efficacy and autonomy over their own health needs was seen as influential to their confidence level, supported self-empowerment and provided reassurance throughout the breastfeeding journey. There was also a desire for more evidence-based information and expectations of health professionals to provide credible and reliable information regarding the use of herbal medicines during breastfeeding. This study has enhanced our understanding of the perspectives and attitudes of breastfeeding women towards the use of herbal medicines, in particular galactagogues, while breastfeeding. The positive attitudes of breastfeeding women identified in this study highlight the need for further research into evaluating the safety and efficacy of commonly used herbal galactagogues, whilst the negative views on breastfeeding education should be taken into consideration when implementing or improving breastfeeding-related health policies.